Analisis Nilai Karakter Peserta Didik di UPTD SMP Negeri 4 Gunungsitoli Selatan - Alirwan Forniat Harefa; Agnes Renostini Harefa (Journal on Education, 2023)
Character education is an effort that is carried out in a planned and sustainable manner and involves all components bound to change and develop one's character and personality, including components of knowledge, awareness or will, and actions taken. Character is a psychological trait, character, morals or a person's character that distinguishes an individual from other individuals. Therefore, this study aims to describe the character values ​​of students at UPTD SMP Negeri 4 Gunungsitoli Selatan. The research was conducted using a descriptive method with a quantitative approach where information will be processed and presented in descriptive form or in the form of sentences. The data collection instrument in this study was using observation sheets, interview transcripts and questionnaires. The results showed that the character of the students at the UPTD SMP Negeri 4 Gunungsitoli Selatan was generally well indicated with an average percentage ranging from 71% -85%, where the character values ​​​​sequentially from the highest percentage were nationalist 84.76%, integrity 80.87 , religious 77.64%, mutual cooperation 77.50%, and the character of independence occupies the lowest position with a percentage of 73.05%.